2017
DOI: 10.3390/w9090661
|View full text |Cite
|
Sign up to set email alerts
|

Effect by Alkaline Flocculation of Algae and Phosphorous from Water Using a Calcined Waste Oyster Shell

Abstract: Alkaline flocculation has been considered as a potential candidate to remove algae and eutrophic substances from water. A number of researches using low-cost and environmentally friendly methods have been suggested to optimize removal efficiency. In this study, a calcium-containing waste oyster shell, as an environmentally friendly substance, has been used to treat phosphorous, a eutrophic substance, and to remove algae from the fresh water simultaneously. The X-ray Fluorescence (XRF) analysis showed that CaO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, the results indicated that part of CaCO 3 was still retained in FB-OS after calcination, which was as like the literature. [47] In addition, it was reported that CaO Thermogravimetric analysis was performed on B-BC-OS and B-FB-OS to observe the impaction of Fe(III)-ball clay on the hightemperature weight loss of oyster shells, the results were shown in Figure 1e,f. It could be observed that the volatilization of free water in the samples before 100 °C.…”
Section: Materials Characterization Results and Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…However, the results indicated that part of CaCO 3 was still retained in FB-OS after calcination, which was as like the literature. [47] In addition, it was reported that CaO Thermogravimetric analysis was performed on B-BC-OS and B-FB-OS to observe the impaction of Fe(III)-ball clay on the hightemperature weight loss of oyster shells, the results were shown in Figure 1e,f. It could be observed that the volatilization of free water in the samples before 100 °C.…”
Section: Materials Characterization Results and Analysismentioning
confidence: 98%
“…However, the results indicated that part of CaCO 3 was still retained in FB‐OS after calcination, which was as like the literature. [ 47 ] In addition, it was reported that CaO could react with SiO 2 to form CaSiO 3 . Fe(OH) 3 was dehydrated at high temperature to form Fe 2 O 3 , and part of Fe 2 O 3 reacted chemically with CaO to form Ca 2 Fe 2 O 5 .…”
Section: Test Results and Analysismentioning
confidence: 99%
“…Shell waste has high porosity, active adsorption sites and a high specific surface area, and thus, it can be used as an efficient and cheap biosorbent. The adsorption efficiency depends on parameters such as the pH of the solution, reaction temperature, contact time, adsorbent dosage and the concentration of metal ions [53][54][55].…”
mentioning
confidence: 99%